Strategies on Service Quality and Development in Using Hajj Savings Products Case Study of Bank Syariah Indonesia KCP Medan Iskandar Muda - Batu Bara, Nazryva Nur Muthia; Tuti Anggraini; Ahmad Perdana Indra (Amkop Management Accounting Review (AMAR), 2025)
The purpose of this writing is to determine the Strategy for Service Quality and Development in Using Hajj Savings Products Case Study of Bank Syariah Indonesia KCP Medan Iskandar Muda. Bank Syariah Indonesia (BSI) as one of the largest Islamic financial institutions in Indonesia has an important role in providing various banking products that are in accordance with sharia principles. This type of research is qualitative with a case study design at Bank Syariah Indonesia KCP Medan Iskandar Muda. In this study, the types of data used consist of primary and secondary data sources, this study uses 3 informants. The results of the study show that improving service quality and adaptive product development strategies play a major role in rebuilding public trust in post-pandemic hajj savings. BSI KCP Medan Iskandar Muda has succeeded in responding to these challenges through the integration of digital services such as the BYOND application, the active implementation of Islamic financial education. Marketing strategies are not only oriented towards the quantity of customers, but also building loyalty based on sharia values. Some of the main factors found in this study are responsive service, clarity of information provided, and ease of administration process. Customers tend to feel more comfortable and confident in saving if they get good service, including friendly employees, speed in handling transactions, and transparency regarding costs and product provisions. This study shows that the strategies implemented by BSI KCP Medan Iskandar Muda in improving the quality of service and developing hajj savings products have provided positive results.